From temperate to polar waters: Transition to non‐cyanobacterial diazotrophy upon entering the Atlantic gateway of the Arctic Ocean - Lisa W. von Friesen; Christien P. Laber; Bjarke H. Kristensen; Emma Nysted; Marcus Sundbom; Stefan Bertilsson; Pauline Snoeijs‐Leijonmalm; Hanna Farnelid; Lasse Riemann (Limnology and Oceanography, 2025)
Nitrogen fixation, the microbial reduction of dinitrogen to ammonia, is increasingly recognized to occur in the Arctic Ocean. However, knowledge about the composition, biogeography, abundance, and ecology of nitrogen‐fixing organisms (diazotrophs) is poor. This ultimately hinders the prediction of ecosystem productivity fueled by nitrogen fixation in this rapidly changing and predominantly nitrogen‐limited ocean. We assessed the composition and abundance of total and nifH ‐expressing diazotrophs in subsurface water (8 m; amplicon sequencing and quantification of the marker gene nifH ) over ~ 3400 km from the mouth of the brackish Baltic Sea to the sea ice edge in the Arctic Ocean. Upon entering nutrient‐rich waters in the Atlantic gateway to the Arctic, we discovered an abrupt transition from autotrophic to heterotrophic diazotrophy ( nifH expression). Our findings therefore suggest that diazotrophy is functionally distinct in the Arctic Ocean compared to adjacent temperate‐boreal waters—a difference likely driven by inorganic nutrients, salinity, and temperature. We identify three key non‐cyanobacterial diazotroph groups in the Arctic Ocean with Arctic‐specific (Rhodocyclales and Oceanospirillales) or more widespread (unknown Gammaproteobacterium) distribution patterns and report their nifH gene transcription levels (up to 10 3 nifH transcripts L −1 ). In contrast, nifH expression in the warmer and more nutrient‐poor Norwegian Sea with coastal‐influenced water was dominated by sublineages of Candidatus Atelocyanobacterium thalassa (UCYN‐A1, UCYN‐A2, UCYN‐A4; up to 10 4 nifH transcripts L −1 ). With ongoing atlantification of the Arctic pushing oceanic provinces and biogeographical ranges poleward, we predict a future displacement of the transition from autotrophic to heterotrophic diazotrophy with likely significant changes in nitrogen fixation.

Colony‐forming and single‐cell picocyanobacteria nitrogen acquisition strategies and carbon fixation in the brackish Baltic Sea - Christien P. Laber; Javier Alegria Zufia; Catherine Legrand; Elin Lindehoff; Hanna Farnelid (Limnology and Oceanography, 2024)
Picocyanobacteria are widespread and globally significant primary producers. In brackish waters, picocyanobacterial populations are composed of diverse species with both single‐cell and colony‐forming lifestyles. Compared to their marine counterparts, brackish picocyanobacteria are less well characterized and the focus of research has been weighted toward single‐cell picocyanobacteria. Here, we investigate the uptake dynamics of single and colony‐forming picocyanobacteria using incubations with dual carbon‐13 and inorganic (ammonium and nitrate) or organic (urea and amino acids) nitrogen‐15 sources during August and September 2020 in the central Baltic Sea. Phytoplankton community and group‐specific uptake rates were obtained using an elemental analyzer isotope ratio mass spectrometer (EA‐IRMS) and nano secondary‐ion mass spectrometry (NanoSIMS). Picocyanobacteria contributed greater than one third of the ammonium, urea, amino acids, and inorganic carbon community uptake/fixation in September but 5 cells mL −1 and represented > 5% of the average phytoplankton biomass, suggesting that they are periodically important for the ecosystem. Colonial strain identification was not distinguishable using 16S rRNA gene amplicon data, highlighting a need for refined tools for identification of colonial forms. This study shows the significance of single‐celled brackish picocyanobacteria to nutrient cycling and the importance of considering uptake and lifestyle strategies when assessing the role of picocyanobacteria in aquatic ecosystems.

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.